Experimental study on the disintegration behavior of red clay under different pH conditions - Wang, Hongming; Liu, Zhikui; Xie, Yongxiong; Li, Shanmei (Frontiers in Materials, 2024)
Soil caves collapse are typical geological hazards in karst areas. The disintegration of red clay is one of the important mechanisms leading to soil caves collapse. The pH of the soil pore solution has changed due to acid rains and the overuse of fertilizers. This study conducted disintegration tests to observe the disintegration rate of red clay in solutions with different pH values by a self-made disintegration apparatus. The inductively coupled plasma mass spectrometer (ICP-MS) and Zeta potential analyzer were used to test the cations concentration in the solutions and the electric potential (ζ potential) of red clay, analyzing the effect of pH on the physicochemical properties and the disintegration rate of red clay, providing a scientific basis for evaluating and preventing soil caves collapse. The results show that the disintegration rate in solutions with different pH values follows the order of pH=11 > pH=9 > pH=3 > pH=5 > pH=7. When pH < 7, the cations concentration and the cations charges density in the soil solutions increased as the pH decreases. The electric potential changed from negative to positive as the pH decreases, with the potential value first decreasing and then increasing. When pH > 7, the cations concentration, cations charges density in the soil solutions, and the electric potential increased with the pH increased. The ratio of charges density to electric potential increased under both acidic and alkaline conditions, the thickness of the clay diffusion layer decreased, short-range gravitational decayed and repulsion increased, ultimately leading to the disintegration of red clay.